PRODUKTIVITAS DAN KONTRIBUSI PENGOLAHAN ANYAMAN PURUN (Lepironia articulatta Domin) TERHADAP PENDAPATAN MASYARAKAT DI DESA SUNGAI RUTAS KABUPATEN TAPIN - Ahmadi Ahmadi; Adi Rahmadi; Fatriani Fatriani (Jurnal Sylva Scienteae, 2019)
ABSTRACT.  This  study  aims  to  determine  the  productivity  and contribution  of woven  purun (Lepironia articulatta Domin) to the income of the community. The method used by observation in central woven craft purun and interview method based on questionnaires on the respondents woven craftsmen purun respondents taken 100% of the number of craftsmen made crafts there are two that is woven mat mats and respondents craftsman mat woven there are 8 people and craftsman woven hat 14 person. Productivity of mats ranges from 0.085 pieces / hour, to 0.101 pieces per hour. The highest productivity of  the respondents was 0.101  fruit/hour,  the  lowest was 0.085 fruit/hour. The productivity of hat making ranges from 1,035 pieces / hour, to 1,364 pieces/hour.  The  highest  productivity  of  Fajarianti  1,364  respondents/hour,  the  lowest  of Asniah 1,035 respondents per hour. Net income making mats ranging from IDR 2,300,000.00 to IDR 2,863,500.00.  The  highest  income  of  respondents  Marsiah  IDR 2.863.500,00  per  year lowest  respondents Dariah IDR 2.300.000,00 per year. Net  income of hat making ranges  from IDR2.180.854,00  to  IDR 3,512,760.00.  The  highest  income respondents  Fajarianti  IDR 3.512.760,00  per  year, the lowest income respondents Salamiah IDR 2,180,354.00 per year.  The contribution of woven mats decreased an average of 30.30%. The highest respondent Laila Hastuti is 36.28%, the lowest respondent  is Arniah 26.44%, the average contribution of the hat is 30.01%. Highest respondent Aisyah is 45.37%, the lowest responder Salamiah is 18.51%  Keywords: purun; productivity; income  ABSTRAK. Penelitian  ini bertujuan untuk mengetahui produktivitas dan kontribusi pengolahan anyaman purun (Lepironia articulatta Domin)  terhadap pendapatan masyarakat. Metode yang digunakan  observasi  di  sentral  kerajinan  anyaman  purun  dan  metode  wawancara  berdasar kuesioner  pada  responden  pengrajin  anyaman  purun  responden  diambil  100%  dari  jumlah pengrajin jenis kerajinan yang dibuat ada dua yaitu kerajinan anyaman tikar dan topi responden pengrajin  anyaman  tikar  ada  8  orang  dan  pengrajin  anyaman  topi  14  orang.  Produktivitas pembuatan tikar berkisar antara 0,085 buah/jam, sampai 0,101 buah/jam. Produktivitas tertinggi responden Arniah 0,101 buah/jam,  terendah Dariah 0,085 buah/jam. Produktivitas pembuatan topi  berkisar  1,035  buah/jam,  sampai  1,364  buah/jam.  Produktivitas  tertinggi  responden Fajarianti  1,364  buah/jam,  terendah  Responden  Asniah  1,035  buah/jam.  Pendapatan  bersih pembuatan  tikar  berkisar  antara  Rp.2.300.000,00  sampai  Rp.2.863.500,00.  Pendapatan tertinggi  responden  Marsiah  Rp.2.863.500,00  pertahun  terendah  responden Dariah  Rp.2.300.000,00  pertahun.  Pendapatan  bersih  pembuatan  topi  berkisar  antara  Rp  2.180.854,00 sampai  Rp.  3.512.760,00.  Pendapatan  tertinggi  responden  Fajarianti  Rp.  3.512.760,00 pertahun,  pendapatan  terendah  responden  Salamiah  Rp.  2.180.354,00  pertahun.  Kontribusi anyaman  tikar  purun  rata-rata  30,30%.  Tertinggi  responden  Laila  Hastuti  sebesar  36,28%, terendah responden Arniah 26,44%, kontribusi topi purun rata-rata 30,01%.Tertinggi responden Aisyah sebesar 45,37% , terendah  responden Salamiah sebesar 18,51%.  Kata kunci : purun; produktivitas; pendapatan